2017
DOI: 10.1142/s2010135x17500382
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of mesoporous photonic crystals, filled with dielectrics, ferroelectrics and piezoelectrics

Abstract: At present, it is very important to create new types of mirrors, nonlinear light frequency transformers and optical filters with controlled optical properties. In this connection, it is of great interest to study photonic crystals. Their dielectric permittivity varies periodically in space with a period permitting Bragg diffraction of light. In this paper, we have investigated the optical properties of mesoporous three-dimensional (3D) opal-type and one-dimensional (1D) anodic alumina photonic crystals, filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Generally, silica (SiO 2 ) particles are used [18], but other ones made of polystyrene (PS) or polymethyl methacrylate (PMMA) can also be exploited [19]. To vary the dielectric contrast and to enlarge the functionality of opal PhCs, the matrices are impregnated with magnetic clusters [20,21], active dielectrics [22][23][24], semiconductors [25][26][27],organic and laser-active materials [28][29][30]. Inverse opals are fabricated by removing PS or PMMA spheres from impregnated matrices [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, silica (SiO 2 ) particles are used [18], but other ones made of polystyrene (PS) or polymethyl methacrylate (PMMA) can also be exploited [19]. To vary the dielectric contrast and to enlarge the functionality of opal PhCs, the matrices are impregnated with magnetic clusters [20,21], active dielectrics [22][23][24], semiconductors [25][26][27],organic and laser-active materials [28][29][30]. Inverse opals are fabricated by removing PS or PMMA spheres from impregnated matrices [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, impregnation of opals with materials with appreciable electrical, magnetic and optical properties is of particular interest for fundamental and applied research. To date, there have already been reports on the electromagnetic field enhancement effect [7], the confinement effect at phase transition [8], the size effect in the vibrational spectrum [9,10] as well as the increase of ionic conductivity in nanocrystalline state [11] for functional materials placed in an array of opal pores. When such matrix nanocomposites are fabricated, usually by melt-based technique, crystallization of the introduced component occurs inside the pores under conditions significantly different from conventional ones.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, most of the studies observed that the nonlinear optical glasses are in general made up of silicate, germinate, chalcogenide and tellurite based glasses doped with metal oxide nanoparticles or rare earth oxides. [1][2][3][4][5][6][7][8] Now, in this work, we explore nonlinear optical properties coupled with dielectric dispersion (polarization) of lithium borate glasses containing two transition metal oxides. Lithium-borate glasses have gained technological importance due to their high transparency for a wide range of wavelengths (200-2500 nm) and low melting point (… 1000 ○ C) compared to that of silicate and germinate glasses.…”
Section: Introductionmentioning
confidence: 99%